Improving relative earthquake locations using surface-wave source corrections. Issue 1 (26th June 2019) - Howe, Michael; Ekström, Göran; Nettles, Meredith
SUMMARY: We develop a procedure to improve estimates of relative earthquake locations using Rayleigh and Love wave arrivals for multiple earthquakes recorded at common stations. We fit predicted differential traveltimes to those measured using a cross-correlation technique, and correct the phases of the cross-correlation functions for phase delays that result from the surface-wave radiation patterns. We develop an empirical measure of uncertainty that provides realistic estimates of the errors in the earthquake locations. We investigate the effectiveness of the relocation procedure by first applying it to two suites of synthetic earthquakes. We then relocate real earthquakes in three separate regions: two ridge-transform systems and one subduction zone. We demonstrate that the inclusion of source corrections in the relocation procedure results in improved location estimates compared to relocations without source corrections. The source correction also allows for automated application of the relocation procedure, even in regions with a wide range of earthquake focal mechanisms.